"It's about having the choice": Stakeholder perceptions of population‐based genetic carrier screening for fragile X syndrome1. Issue 1 (13th December 2012) - Archibald, Alison D.; Hickerton, Chriselle L.; Jaques, Alice M.; Wake, Samantha; Cohen, Jonathan; Metcalfe, Sylvia A.
Abstract This project explored, the views of key stakeholders regarding population‐based genetic carrier screening for fragile X syndrome (FXS). Interviews and focus groups were conducted with healthcare providers, relatives of individuals with FXS and members of the general population. Data were transcribed verbatim and coded into themes. 188 individuals took part in this study. Perceived benefits of carrier screening included: learning the risk of having a child with FXS; learning the risk of fragile X‐associated primary ovarian insufficiency; and the opportunity for carriers to access reproductive options. Concerns included: the emotional impact of screening and receiving a carrier result; the predictive testing nature of the carrier test with respect to fragile X‐associated tremor/ataxia syndrome; potential confusion created by receiving an intermediate result; and implications of genetic screening for society. Overall, population‐based genetic carrier screening was perceived to be acceptable provided it is optional and offered at an appropriate stage of life. With the support of the participants to promote individual choice by offering a population‐based carrier screening program for FXS, it is essential to carefully consider how screening might be offered in order to ensure broad accessibility and facilitation of decision‐making. © 2012 Wiley Periodicals, Inc.